2008
DOI: 10.5194/aab-51-266-2008
|View full text |Cite
|
Sign up to set email alerts
|

Tissue composition of carcass, meat quality and fatty acid content of ducks of a commercial breeding line at different age

Abstract: Composition of carcasses and meat quality were investigated in ducks from A44 strain from the 7 th to 9 th week of life. Drakes and ducks in the 8 th and 9 th week of age were characterized by significantly higher dressing percentage and better musculature than in the 7 th week. Fatness of drakes and ducks carcasses significantly increased in the 8 th and 9 th week of rearing and the meat : fat ratios were similar to the results obtained in ducks of the 7 th week of age. Basing on pH values, faulty meat of PSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
36
4
8

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 8 publications
10
36
4
8
Order By: Relevance
“…Under standard feeding conditions, total SFA compared to monounsaturated fatty acids (MUFAs) and PUFA is high and accounts for up to 49.4 % (Kokoszynski and Bernacki, 2010;Kokoszynski, 2011). Meanwhile, n-3 PUFA in the breast muscles is very low; only traces have been reported by Witak (2008). In breast and leg muscles, the PUFA / SFA ratio ranged from 0.22 to 0.42 (Kokoszynski, 2011) and n-6 / n-3 ratios ranged from 7.08 to 10.07 (Witak, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under standard feeding conditions, total SFA compared to monounsaturated fatty acids (MUFAs) and PUFA is high and accounts for up to 49.4 % (Kokoszynski and Bernacki, 2010;Kokoszynski, 2011). Meanwhile, n-3 PUFA in the breast muscles is very low; only traces have been reported by Witak (2008). In breast and leg muscles, the PUFA / SFA ratio ranged from 0.22 to 0.42 (Kokoszynski, 2011) and n-6 / n-3 ratios ranged from 7.08 to 10.07 (Witak, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, n-3 PUFA in the breast muscles is very low; only traces have been reported by Witak (2008). In breast and leg muscles, the PUFA / SFA ratio ranged from 0.22 to 0.42 (Kokoszynski, 2011) and n-6 / n-3 ratios ranged from 7.08 to 10.07 (Witak, 2008). Nguyen et al (2003) indicated that the composition of intramuscular fatty acids in monogastric animals depends on their feed composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical changes that occurred during the first 24 h postmortem are very important for the meat quality, including the decrease in pH 24 , which shows that the glycolysis process is occurring in a normal way; thus, this factor is an important parameter for the preservation and stability of meat (15,28,29). Witak (27) stated that the average pH 24 at 24 h postmortem was 5.75 and 5.77 in breast meat and 5.91 and 5.94 in thigh meat of male and female A44 ducks, respectively. Although in the present study the pH 24 of breast meat was exactly the same in both sex groups, the pH 24 of thigh meat was higher than in that previous study.…”
Section: Meat Composition and Phmentioning
confidence: 99%
“…Duck meat and its products are highly appreciated by customers worldwide (Kim et al 2016). Moreover, duck meat and its products have gained increased consumer interest since it is recommended to reduce the intake of red meat, which has been related to cardiovascular disease (Adzitey et al 2012;Witak, 2008;Zou et al 2017b). The consumption of duck meat and its products has increased about twofold in China between 2000 and 2011 (Wang et al 2013;Wang et al 2016;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%